The research on the negative evaluation anxiety of taekwondo players by different variables - Atasoy, M.; Karabulut, E. O.; Var, L. (Turkish Journal of Sport and Exercise, 2018)
This research, focused on the examination of the negative evaluation anxiety of taekwondo players studying at university by different variables, is a scanning method research. This research is carried out on the players joining in Turkey Taekwon-do Championship which was held on Ahi Evran University physical education and sport faculty at 2017 by the federation of turkey intercollegiate sports. The population of study consists of 399 players joining the championship, and the research sample consists of 228 volunteer players who are 93 female and 135 male players. ``Negative Evaluation Anxiety Scale`` developed by Leary 1983), transcribed in Turkish by Çetin and friends was used as a data collection tool. Frequency (n) and percentage (%) depictive statistical methods was used for personal information at analyzing of the data. For the evaluation of scales, T test one of the parametric tests was used at pair groups, anova test was used at multiple groups and significance level of .05 was chosen for the statistical significance. It is determined at the result of research that the negative evaluation anxiety of Elit University taekwondo players show difference related to factors which are being national player or not and gender, and don`t show difference related to factors which are weight and the grade of sport.